The Influence of Price and Quality of Broiler Chicken on Consumer Purchase Decisions at the Mattirowalie Traditional Market, Barru Regency - Aisyah Aisyah; Dhian Ramadhanty; Rina Angriani (International Forum of Researchers and Lecturers, 2024)
Consumers in making purchases always consider matters related to the price and quality of a product to be purchased, some people do not prioritize quality over price but some other people make quality a consideration in purchasing broiler meat. This study aims to determine the effect of price and quality of broiler chicken on consumer purchasing decisions at Mattirowalie market. This research was conducted at Mattirowalie market, Barru Regency, South Sulawesi in March-April 2024. This study uses quantitative data obtained from observations of distributing questionnaires with 100 respondents, the data were analyzed using multiple linear regression with the help of SPSS version 26. The results showed that the results of multiple linear regression analysis of price variables had a negative or reciprocal effect and the quality of broiler chicken had a positive or unidirectional effect on consumer purchasing decisions. Partially shows that the price and quality of broiler chickens have a significant effect on consumer purchasing decisions while simultaneously the price and quality of broiler chickens together have a significant effect on consumer purchasing decisions. The coefficient of determination of the price and quality of broiler chicken is 56% on consumer purchasing decisions in the Mattirowalie market while the remaining 44% is influenced by other factors outside of the study.